The Correlation Between Students English Proficiency and Their Academic Achievement at Assalam Orphanage - St. Nur Aima Fatima; Yohanes Olak Langodai; Nasrul Nasir (English Education Postgraduate Program, Universitas Negeri Manado, 2025)
The objective of this research was to find out whether or not there was a correlation between differentiated learning and students English scores The research was conducted at UPT SMAN 14 Jeneponto with data collected through questionnaires distributed to students and from English teachers The results of the correlation analysis using the Pearson Product Moment showed a correlation coefficient of 0 522 indicating a quite strong correlation between differentiated learning and students English scores This suggests that differentiated learning had a positive influence on students academic performance in English Although the correlation was not very strong the findings indicated that when students were taught according to their individual needs interests and learning styles their English achievement tended to improve It can be concluded that differentiated learning contributed to students English learning outcomes < em>< p>